Highly sensitive SERS analysis of the cyclic Arg–Gly–Asp peptide ligands of cells using nanogap antennas. Issue 2 (2nd May 2016) - Portela, Alejandro; Yano, Taka‐aki; Santschi, Christian; Martin, Olivier J. F.; Tabata, Hitoshi; Hara, Masahiko
Abstract : The cyclic RGD (cRGD) peptide ligands of cells have become widely used for treating several cancers. We report a highly sensitive analysis of c(RGDfC) using surface enhanced Raman spectroscopy (SERS) using single dimer nanogap antennas in aqueous environment. Good agreement between characteristic peaks of the SERS and the Raman spectra of bulk c(RGDfC) with its peptide's constituents were observed. The exhibited blinking of the SERS spectra and synchronization of intensity fluctuations, suggest that the SERS spectra acquired from single dimer nanogap antennas was dominated by the spectrum of single to a few molecules. SERS spectra of c(RGDfC) could be used to detect at the nanoscale, the cells' transmembrane proteins binding to its ligand. SERS of cyclic RGD on nanogap antenna. Abstract : Understanding the interactions of different cancer's cell ligand‐receptor constitutes a major challenge for biophotonics research. Using Surface Enhanced Raman Spectroscopy (SERS) the current study experimentally investigates the extracellular matrix (ECM) ligand: Arg–Gly–Asp (RGD) in its cyclic configuration, using the high spatial resolution provided by a single gold plasmonic nanogap antenna. The SERS spectrum of the polypeptide used in multiple drug delivery systems is presented and analysed in details.